1993
DOI: 10.1159/000154131
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Groups and Cirrhosis of the Liver

Abstract: Haptoglobin (HP) groups were determined in Chinese patients suffering from eight different diseases and compared to those of 552 control subjects. Patients with cirrhosis of the liver showed a significant difference from controls in the distribution of HP types (p = 2 × 10–4), with increases in the HP*1 allele and HP1-1 phenotype frequencies. The relative risk for the HP1-1 phenotype was 3.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…In this study a significant increase in the frequency of Hp1-1 phenotype was observed among patients with all three liver diseases including liver cirrhosis which agrees with (Blenk et al, 1978;Zhao et al, 1993), but disagreed with (Vitalis et al, 2011). Therefore, it is reasonable to conclude that individuals with Hp1-1 phenotypes might be more susceptable to liver cancer than individuals with other Hp phenptypes however, this needs more confirmation at the molecular and immunological levels…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study a significant increase in the frequency of Hp1-1 phenotype was observed among patients with all three liver diseases including liver cirrhosis which agrees with (Blenk et al, 1978;Zhao et al, 1993), but disagreed with (Vitalis et al, 2011). Therefore, it is reasonable to conclude that individuals with Hp1-1 phenotypes might be more susceptable to liver cancer than individuals with other Hp phenptypes however, this needs more confirmation at the molecular and immunological levels…”
Section: Discussionsupporting
confidence: 85%
“…found that people with Hp1-1 phenotype are more susceptible to falciparum malaria and to development of severe complications, the same phenotype was also associated with other different liver diseases such as those with liver cirrhosis who showed a significant difference from controls in the distribution of Hp types, with increases in the Hp*1 allele and Hp1-1 phenotype frequencies (Zhao et al, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…et al, 2000) and type II (Nakhoul et al, 2001) diabetes. Zhao and Zhang (1993) found that Hp1‐1 was over‐represented in 107 patients with cirrhosis of the liver compared with 552 normal adults (relative risk 3·3, P = 2 × 10 −4 ). Zipprich et al (1986) found an increased frequency of Hp1‐1 in 100 German patients with chronic, non‐alcoholic liver disease but not in 90 patients with cirrhosis when compared with 1726 control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,32,40 As previously reported, several studies have demonstrated that Hp phenotypes play a role in sparing Hb. 27,[50][51][52] This protein expresses three phenotypes with different affinities to bind to Hb. Hp 1.1 has a higher Hb-binding ability than the 2.2 and 2.1 phenotypes and limits Hb elimination by the liver.…”
Section: Discussionmentioning
confidence: 99%